Assessment of Healthcare Workers' Knowledge to Occupational hazards in Some Hospitals of Thi-Qar Governorate /Iraq - alwshah, mohamed; Mahmood Salim Thamer,; Ali Ghanim Gatea, (University of Thi-Qar Journal of Science, 2023)
Employees in the healthcare industry operate in one of the riskiest workplaces Healthcare employees suffer a number of dangers as a result of their job last activities in addition to the usual workplace-related risks. These risks come from a variety of sources including biological, physical, psychological, and chemical agents. The study's objectives were to investigate the levels of knowledge held by medical and paramedical personnel regarding occupational dangers in their workplaces. Moreover, the relationships between various demographic characteristics of these staff members and their knowledge of such hazards were investigated. A descriptive cross-sectional study was carried out in hospitals, During the period of November 5th, 2022 to February 10th, 2023. A number of 355 people were participated in the study, information about (Knowledge) the data was collected through a structured questionnaire and the data was collected using self-report Technique. Regarding the Knowledge, the results of the present study showed that all responses regarding the preceding domain had a moderate evaluation. Also, the result show that the health care worker knowledge impact with education level and the year of age and year of experience. Depending on the collected results, it can be concluded that the medical and paramedical staff had below good (moderate) Knowledge regarding the occupational hazards in their working environment.